RELEVANSI PEMIKIRAN IMAM AL-GHAZALI TENTANG EKONOMI ISLAM DI INDONESIA - Fudaili, Muhammad; Rofiah, Khusniati (AMAL: Jurnal Ekonomi Syariah, 2023)
AbstractThis article discusses Islamic economic thought according to Imam al-Ghazali and looks at its relevance in Indonesia. The article uses qualitative research in the nature of a literature study. This study focuses on epistemology from the perspective of the philosophy of science. By using a library study method through scientific articles obtained from online journal publications and related books. Through in-depth study, it shows that in general Imam Al-Ghazali's economic thought provides ethical and moral foundations that are relevant for the development of the Islamic economic system. These concepts can help shape economic policies that take Islamic values into account and create a more just and sustainable society. The implementation of the economic system in Indonesia based on al-Ghazali's thoughts emphasizes the importance of justice in the distribution of wealth. This principle can guide the formation of economic policies that reduce social inequality. al-Ghazali understood the concepts of zakat and sadaqah as instruments to reduce inequality and help those in need. This concept is in line with the principles of zakat and sadaqah in Islamic economics which support community welfare.Keywords: Relevance Islamic Economics, al-Ghazali. AbstrakArtikel ini mendiskusikan tentang pemikiran ekonomi Islam menurut Imam al-Ghazali dan melihat relevansinya di Indonesia. Artikel menggunakan penelitian kualitatif yang bersifat studi kepustakaan. Studi ini meemfokuskan pada epistemologi dari segi filsafat ilmu. Dengan menggunakan metode menggunakan metode studi kepustakaan melalui artikel-artikel ilmiah yang diperoleh dari terbitan jurnal-jurnal secara online dan buku-buku yang terkait. Melalui kajian mendalam menunjukkan bahwa secara umum pemikiran ekonomi Imam Al-Ghazali menyajikan fondasi etika dan moral yang relevan untuk pengembangan sistem ekonomi Islam. Konsep-konsep ini dapat membantu membentuk kebijakan ekonomi yang memperhatikan nilai-nilai Islam dan menciptakan masyarakat yang lebih adil dan berkelanjutan. Penerapan sistem ekonomi di Indonesia berdasarkan pemikiran al-Ghazali menekankan pentingnya keadilan dalam distribusi kekayaan. Prinsip ini dapat membimbing pembentukan kebijakan ekonomi yang mengurangi kesenjangan sosial. Al-Ghazali memahami konsep zakat dan sadaqah sebagai instrumen untuk mengurangi ketidaksetaraan dan membantu mereka yang membutuhkan. Konsep ini sejalan dengan prinsip-prinsip zakat dan sadaqah dalam ekonomi Islam yang mendukung kesejahteraan masyarakatKata Kunci: Relevansi, Ekonomi Islam, al-Ghazali